ANALISIS BENTUK TEMA DAN NILAI MORALITAS DALAM NOVEL PUTUS CINTA BUKANLAH AKHIR SEGALANYA KARYA IDA RAIHAN - Yosefina Ledia Namun; I Nyoman Suparsa; A.A. Rai Laksmi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
This research is a qualitative descriptive study that aims (1) to determine the structure of the themes and moral values contained in the novel Putus Cinta Is Not the End of Everything. The theories that underlie this research are (1) the nature of literary works, (2) the definition of novels, (3) the intrinsic elements of the novel, (4) the structure of the theme, and (5) the notion of morality values. Data collection is done by the library method. The data in this study were processed by using qualitative analysis techniques, namely, the researchers conducted the analysis interactively and took place continuously until it was finished. This study uses an instrument that is a tool used by research in collecting data so that it is arranged systematically. There are also steps in data analysis using data triangulation analysis, namely: (1) reducing data, (2) presenting data and (3) data verification. The results of this study indicate the findings of two theme structures, namely major themes and minor themes. The major themes found are the major themes of love and problems with her two older sisters, while the minor themes are friendship, the sincerity of a friend. The novel "Putus Cinta Is Not the End of Everything" by Ida Raihan also contains twelve moral values, namely the value of struggle, the value of sacrifice, the value of injustice, the value of doubt, the value of crime, the value of caring, the value of independence, the value of honesty, the value of discipline, the value of politeness, the value of politeness. , the value of courage, the value of purity of heart.